Implementasi Asuhan Sayang Ibu di Wilayah Kerja Puskesmas Candimulyo Kabupaten Magelang pada Bulan Mei Tahun 2013 - Iswari Paramita; Mustika Pramestyani; Mentari Mentari (Journal of Health (JoH), 2015)
Background: Dear mother care is care with the principle of mutual respect for the culture, beliefs and desires of the mother. One basic principle is to include husbands and families during labor and childbirth. Attention and support to the mother during labor will gain a sense of security and a better output. Dear mother's care during childbirth include the care given to the mother, which began when I to stage IV. Dear mother care implementation or become a fundamental principle in the provision of care dear mother in the delivery process includes providing emotional support, provision of fluids and nutrition, flexibility for bladder and bowel, as well as the prevention of infection. Objective: This study aims to determine the implementation dear mother care clinic working area Candimulyo. Method: Type of approach used in this study is the evaluation of research method (Evaluation Study). Respondents in this study all private midwives working area clinic Candimulyo 20 the number of samples taken by the Non-Probability sampling techniques saturated. Result: From the analysis of the implementation of the care of dear mother of this study showed that of the 20 respondents found the overall implementation of the care of maternal affection are quite as many as 13 respondents (65%). Conclusion: Implementation dear mother care clinic Candimulyo working area is quite.